2013
DOI: 10.3390/ijms14022242
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Product (AGE)-AGE Receptor (RAGE) System Upregulated Connexin43 Expression in Rat Cardiomyocytes via PKC and Erk MAPK Pathways

Abstract: The remodeling of cardiac gap junction contributes to the arrhythmias in a diabetic heart. We previously reported that high glucose reduced Cx43 protein level in neonatal rat cardiomyocytes. But, the effect and mechanisms of advanced glycation end product (AGE) on Cx43 expression still remain unclear. In this study, we measured the AGE receptor (RAGE) and Cx43 expression by immunohistochemisty in AGE-infused Sprague-Dawley (SD) rats. In vitro, the Cx43 and RAGE levels were detected in AGE-treated cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 48 publications
0
16
2
Order By: Relevance
“…We found that the RAGE levels were unaffected by AGEs in BME, in contrast to others who have observed the upregulation of RAGE levels by AGEs [44,50]. However, most of these studies used exogenous AGE preparations dissimilar to the BME-bound AGEs in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…We found that the RAGE levels were unaffected by AGEs in BME, in contrast to others who have observed the upregulation of RAGE levels by AGEs [44,50]. However, most of these studies used exogenous AGE preparations dissimilar to the BME-bound AGEs in our study.…”
Section: Discussioncontrasting
confidence: 93%
“…Classical PKCs (including the α, β1, β2, and γ isoforms) are calcium-dependent, novel PKCs (including the δ, ε, η, and θ isoforms), and atypical PKCs (including the ξ, λ, and τ isoforms) are calcium independent. Several studies have shown that the PKC family, mainly classical PKCs, are implicated in Cx43 phosphorylation at multiple serines (S365, S368, S369, S372, and S373) [36,37], expression [38] and GJIC regulation [39][40][41]. We found, for the first time, that inhibition of PKC pathways by GF109203X could also block MC proliferation ( Fig.…”
Section: Effects Of Aldo On the Intracellular Calcium Concentrationsmentioning
confidence: 49%
“…This may explain the non-significant changes in RAGE expression on tissues studied because the RAGE protein could be expressed in other isoforms such as sRAGE. In addition to that, AGE-mediated up-regulation of RAGE expression is dependent on the exposure duration and concentration of AGE [48]. Since there was no significant difference in AGE level among the groups in the present study, AGEmediated increase in RAGE expression was not significant as well.…”
Section: Rage Gene In Rats Undergoes Various Alternative Splicing Andcontrasting
confidence: 47%